2019
DOI: 10.1002/tea.21591
|View full text |Cite
|
Sign up to set email alerts
|

Accessed or latent resources? Exploring new secondary science teachers' networks of resources

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…While the use of social network analysis in science education research is growing (e.g., Fortus et al, 2019; Navy, Nixon, Luft, & Jurkiewicz, 2020), it remains limited, and much of the research on technology‐ and social media‐based networks is primarily descriptive (Macià & García, 2016). While descriptive uses of social network analysis are valuable, if researchers wish to design or impact social networks, a focus upon social network processes may be particularly important—including selection processes to interrogate who interacts with whom and influence processes to understand how involvement in interactions or relationships matter.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of social network analysis in science education research is growing (e.g., Fortus et al, 2019; Navy, Nixon, Luft, & Jurkiewicz, 2020), it remains limited, and much of the research on technology‐ and social media‐based networks is primarily descriptive (Macià & García, 2016). While descriptive uses of social network analysis are valuable, if researchers wish to design or impact social networks, a focus upon social network processes may be particularly important—including selection processes to interrogate who interacts with whom and influence processes to understand how involvement in interactions or relationships matter.…”
Section: Discussionmentioning
confidence: 99%
“…Interesting teaching videos can ensure the enthusiasm of teaching, and the content that can be remembered can reduce the cognitive complexity of students [11].…”
Section: Teaching Resource Basementioning
confidence: 99%
“…This is the part of forming a professional madrasah teacher. In their research, Navy, Nixon, Luft, & Jurkiewicz. (2019) revealed that social resources are very important for teachers.…”
Section: Discussionmentioning
confidence: 99%